2021
DOI: 10.1038/s41598-021-93222-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional virtual histology in unprocessed resected tissues with photoacoustic remote sensing (PARS) microscopy and optical coherence tomography (OCT)

Abstract: Histological images are critical in the diagnosis and treatment of cancers. Unfortunately, current methods for capturing these microscopy images require resource intensive tissue preparation that may delay diagnosis for days or weeks. To streamline this process, clinicians are limited to assessing small macroscopically representative subsets of tissues. Here, a combined photoacoustic remote sensing (PARS) microscope and swept source optical coherence tomography system designed to circumvent these diagnostic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Considering the training data preparation, required for the supervised learning framework implementation, such approach allowed us pixel registration matching between the fluorescence input images and the corresponding brightfield H&E images. In this sense, our used strategy is slightly different from samples preparation workflow reported in 5,12,34,35 permitting avoidance of the sample handling process that involves measurement of the unstained slide first, staining the same slide with H&E, coversliping it and measuring it once more, in order to get a match between the VS tissue structure and stained with H&E. Instead, we used an unpaired image to image translation (refered as to stage 4) . Results of stage 4 VS, using unstained deparaffinized section of a soft tissue sarcoma from a cat onto which transfer learning protocol was applied, produced VS images that partially resembled H&E stained section but had suboptimal contrast between red and blue colors and were blurry.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the training data preparation, required for the supervised learning framework implementation, such approach allowed us pixel registration matching between the fluorescence input images and the corresponding brightfield H&E images. In this sense, our used strategy is slightly different from samples preparation workflow reported in 5,12,34,35 permitting avoidance of the sample handling process that involves measurement of the unstained slide first, staining the same slide with H&E, coversliping it and measuring it once more, in order to get a match between the VS tissue structure and stained with H&E. Instead, we used an unpaired image to image translation (refered as to stage 4) . Results of stage 4 VS, using unstained deparaffinized section of a soft tissue sarcoma from a cat onto which transfer learning protocol was applied, produced VS images that partially resembled H&E stained section but had suboptimal contrast between red and blue colors and were blurry.…”
Section: Resultsmentioning
confidence: 99%
“…According to these possible implementations, several OCT scanner designs have been investigated ( Figure 1 ): handheld imaging probes [ 22 , 23 , 24 , 36 ], surgical instrumentation (e.g., biopsy needle) [ 9 , 10 , 11 ], microscope-integrated systems [ 20 , 43 , 44 ] and non-portable stationary OCT systems [ 25 , 45 , 46 ] that can be used in histopathological studies as a part of hybrid optical imaging systems providing label-free histology [ 47 ]. Considering multifunctionality of OCT in neurosurgery, the multipurpose device with a particular set of OCT probes could be preferred.…”
Section: Clinical Oct Devicesmentioning
confidence: 99%
“…Over the past few years, PARS has emerged as a powerful contender in the label-free histological imaging space 34 36 , 38 . PARS may emulate current histochemical staining, by targeting the UV absorption of DNA (analogous to hematoxylin staining) 34 , 35 , and by targeting the 420 nm absorption of cytochromes (analogous to hematoxylin staining) 34 . Recent works have shown that PARS may offer high contrast and high spatial resolution in freshly resected tissue, formalin fixed tissue, and FFPE tissue sections 35 , 36 .…”
Section: Introductionmentioning
confidence: 99%
“…PARS may emulate current histochemical staining, by targeting the UV absorption of DNA (analogous to hematoxylin staining) 34 , 35 , and by targeting the 420 nm absorption of cytochromes (analogous to hematoxylin staining) 34 . Recent works have shown that PARS may offer high contrast and high spatial resolution in freshly resected tissue, formalin fixed tissue, and FFPE tissue sections 35 , 36 . In resected tissues, PARS has even been shown to provide 3D imaging of subsurface nuclei 35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation